PENGARUH LINGKUNGAN KERJA TERHADAP KUALITAS PELAYANAN PADA DINAS PANTI SOSIAL LANJUT USIA KOTA BIMA PROVINSI NTB - Muh. Zinedin Zidan; Wulandari Wulandari; Muhammad Yusuf (Journal MISSY (Management and Business Strategy), 2022)
Public sector organizations are required to provide excellent service by making customer satisfaction the main goal for service personnel in accordance with public service standards in Law no. 25 of 2009 concerning Public Services. In addition to improving service quality through excellent service, public organizations must also provide quality services with the concept of "wholehearted service". This wholehearted service is reflected in the sincerity of the apparatus to serve with emotion, character, belief in values, points of view, and feelings and makes customer satisfaction the main goal. Based on the results of the research and discussion, the conclusions of the research results can be stated that the work environment has a significant and influential effect on the quality of services at the Service for Elderly Social Institutions in Bima City, NTB Province. The direction of the relationship shows that if the work environment variable is getting better, the service quality variable (Y) is also increasing. The work environment is everything that is around the workers and that can affect them in carrying out the tasks assigned to them.